Tinnitus and Otosclerosis: An Exploratory Study about the Prevalence, Features and Impact in Daily Life - Lima,Antonio Fontes (2022)
Abstract Introduction Tinnitus is experienced by a significant part of the patients suffering from otosclerosis. Objective To assess the prevalence of tinnitus in otosclerosis, its main features, and the impact on the daily life. Methods Patients diagnosed with otosclerosis in 2019 in a tertiary hospital were enrolled in the study. Demographic data were retrieved and, besides a regular audiometric evaluation, the patients underwent acuphenometry to assess the psychoacoustic measurements (pitch and loudness), and the Tinnitus Handicap Inventory (THI). Results In total, 66 patients fulfilled the inclusion criteria, with a female predominance (63.6%; n = 42), and a mean age of 48.7 years. The mean air-bone gap was of 26.3 dB. A total of 72.7% complained of tinnitus; it was mostly unilateral, identified in the low frequencies, namely 500 Hz, with median loudness of 7.5 dB. The median score on the THI score was of 37; most patients had a mild handicap (33.3%, n = 16), followed by those with a severe handicap (22.9%; n = 11). The female gender had a statistically significant association with the presence of tinnitus. The THI scores were higher in middle-aged patients (age groups: 40 to 49 and 50 to 59 years), which was statistically significant. No correlation was found between audiometry results and the prevalence of tinnitus or score on the THI. On the other hand, high-pitched tinnitus, compared to low pitched-tinnitus, was associated with larger air-bone gaps. Conclusion The prevalence of tinnitus in our population was in line with the prevalences reported in the literature. It caused a catastrophic handicap in 22.9% of the patients. High-pitched tinnitus was associated with higher handicap. Nonetheless, the existence of tinnitus and its severity were not associated with the degree of hearing loss.